Fintech and Income Inequality Nexus: Can Financial Inclusion and Financial Freedom Help to Achieve SDGs - Muhammad Rizwan Nazir; Hashir Hussain; Muhammad Imran Nazir; Rabia Umer (Indus Journal of Social Sciences, 2025)
Although theory proposes that financial market imperfections such as information asymmetries, market segmentation and transaction costs prevent poor people from escaping poverty by limiting their access to formal financial services, new financial technologies (Fintech) are seen as key enablers of financial inclusion. Indeed, the UN 2030 Agenda for Sustainable Development (UN-2030-ASD) highlights the importance of harnessing the potential of Fintech to reduce financial exclusion and income inequality. An examination was conducted using data collected for 155 developing countries between 2000 and 2023. The classification of these nations was based on the IMF country categorization outlined in the World Economic Outlook (2023). Information regarding Fin-Tech, Income Inequality, digital financial inclusion variables, financial freedom metrics, governance criteria and various other macroeconomic indicators was sourced from the World Development Indicators (WDI), the Standardized World Income Inequality Database known as SWIID, the Heritage Foundation Economic Freedom Index and the IMF Financial Access Survey (FAS). Robustness check is also applied for improved results. In analysis, the Fintech is negatively correlated with income inequality indicating potential areas where decreasing inequality can be observed. The moderating effect of financial freedom and financial Inclusion has negative effect on this relationship indicating that it helps Fintech in mitigating income disparities. Policymakers, financial institutions and technology providers can benefit from these results and can contribute to the society.